Constructing identities in the workplace through request e-mail discourse – how does one benefit from it? - Victor Ho, (Penerbit UKM, 2010)
This paper discusses the construction of personal identities through the request e-mail discourse by a group of professional English language teachers of a public education institution in Hong Kong. Facing the downsizing of the civil service, the revised appraisal system, and the tighter budget of the Hong Kong SAR government following the Asian financial crisis, teachers working in Hong Kong public schools have less chances of getting promotion and pay rises. To put themselves in an advantageous position in relation to get a promotion and a pay rise, as argued in this paper, the teachers constructed two personal identities online before their peers and superiors in their workplace. A total of 50 e-mails met the two criteria that follow and formed the corpus of the present study: containing at least one request, and having teachers of the same rank as the author and recipients. The request e-mail discourse is analyzed at the clause level with respect to transitivity, mood and modality by drawing upon systemic functional linguistics. It is found that the teachers, using the resources available in the English language grammar, constructed for themselves the identity of a responsible, hardworking member, and of a member with authority and power. This paper hopes to achieve three aims – (1) to contribute to the understanding of the constitutive effect of discourse; (2) to illustrate how such effect could be manipulated by discourse producers in order to achieve both their communicative and political aims; and (3) to enhance people’s e-mail communication competency in the workplace.